2020
DOI: 10.1097/jom.0000000000002039
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Heat Index and Ultraviolet Index on COVID-19 in Major Cities of Pakistan

Abstract: Introduction: The world population is under the grip of global pandemic of COVID-19. The present study analyzed relationship between meteorological parameters and COVID-19 in three major cities of Pakistan, that is, Karachi, Lahore, and Peshawar. Methods: The impacts of heat index (HI) and ultraviolet index (UVI) over daily COVID-19 cases have examined to identify its transmission and propagation. The significance of basic reproductive number ( R … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…These all meteorological parameters significantly impacted to lessen the COVID-19 projection over the Punjab province. The same results have been obtained by Adnan et al 2020 over the major cities of Pakistan. Moreover, the aerosol concentration was high during May and June due to which the COVID-19 cases increased rapidly during these two months.…”
Section: Geo-spatial Analysissupporting
confidence: 88%
See 1 more Smart Citation
“…These all meteorological parameters significantly impacted to lessen the COVID-19 projection over the Punjab province. The same results have been obtained by Adnan et al 2020 over the major cities of Pakistan. Moreover, the aerosol concentration was high during May and June due to which the COVID-19 cases increased rapidly during these two months.…”
Section: Geo-spatial Analysissupporting
confidence: 88%
“…More importantly, weather also played a significant role to subside the COVID-19 cases after the mid-June, 2020. Recent study shows heat index (temperature, humidity) and ultraviolet index played significant role to subside COVID-19 over major cities of Pakistan including Lahore (Adnan et al 2020 ). The cities of Lahore and Islamabad are the hub of business, financial and government functionaries, and the majority of the population traveled there each day from the neighboring regions.…”
Section: Geo-spatial Analysismentioning
confidence: 99%
“…Although the effects of climate variables on COVID-19 activity varied among different country populations, time units, and analytical methods, there were also similar results in the included studies, and especially most of the literature showed that higher temperatures may have largely influenced the spread of coronavirus and suppressed the pandemic. Among the included studies, fifty-eight studies explored the relationship between temperature and COVID-19 transmission, but only one study investigated the heat index, which was found to be positively correlated with the daily basic reproductive number (R 0 ), growth rate, and doubling time (Adnan et al 2021 ). Additionally, another study adopted the mean equivalent temperature and found it to be a noninfluential factor on COVID-19 activity (Jamshidi et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…While case counts are subject to the influence of reporting delay and underreporting, which vary across locations and are thus difficult to control, the reproduction number is a direct estimate of the transmission rate of SARS-CoV-2, quantifying the average number of infections caused by one infection in the population. A small number of studies previously analyzed the association between temperature, humidity, or UV radiation and reproduction number 20 22 , 30 . Wang et al found that a 1 °C increase in temperature was associated with a reduction in the effective reproduction number of 0.026 in China and 0.020 in the U.S., and a 1% increase in RH was associated with a reduction in the effective reproduction number of 0.0076 in China and 0.0080 in the U.S. 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al found that a 1 °C increase in temperature was associated with a reduction in the effective reproduction number of 0.026 in China and 0.020 in the U.S., and a 1% increase in RH was associated with a reduction in the effective reproduction number of 0.0076 in China and 0.0080 in the U.S. 20 . Adnan et al reported a significant negative association between UV index (a standard measurement of the strength of sunburn-producing UV radiation) and basic reproduction number in major cities of Pakistan 30 . These associations are consistent with our findings but were not supported by two studies in China that examined the basic reproduction number: the first found no association between temperature or UV radiation and SARS-CoV-2 transmission 22 ; the second found no association between absolute humidity and SARS-CoV-2 transmission 21 .…”
Section: Discussionmentioning
confidence: 99%